ICP22/IE63 Mediated Transcriptional Regulation and Immune Evasion: Two Important Survival Strategies for Alphaherpesviruses - He, Qing; Wu, Ying; Wang, Mingshu; Chen, Shun; Jia, Renyong; Yang, Qiao; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Zhang, Shaqiu; Huang, Juan; Ou, Xumin; et al. (Frontiers in Immunology, 2021)
In the process of infecting the host, the alphaherpesviruses have derived a series of adaptation and survival strategies, such as latent infection, autophagy and immune evasion, in order to survive in the host environment. Infected Cell Protein 22 (ICP22) is a post-translational modified multifunctional viral regulatory protein encoded by all alphaherpesvirus. In addition to playing an important role in the efficient use of host transcription equipment, it also plays an important role in the defense process of the virus overcoming the host immune system. These two effects of ICP22 are important survival strategies for the alphaherpesviruses. In this review, we summarized the complex mechanism by which ICP22 protein regulates the transcription of a-herpesviruses and its host genes and the mechanism by which ICP22 participates in immune escape. It will also help us understand the pathogenesis of alpha herpes virus infections and provide new strategies to combat these viral infections.